CP-051 An audit to determine the impact of pharmacist medication reconciliation on discharge (MROD) within a tertiary cardiac centre. (14th February 2016) - Fhadil, S; Wright, P; Antoniou, S
Abstract : Background: Waiting for medication at discharge is often quoted as a key factor for delaying patients leaving hospital 1 . The rate limiting step in provision of medication at discharge is preparation of a medication list, from which pharmacy provide a supply. Preparation of a discharge summary (TTA) is completed and validated by junior medical staff after completing clinical tasks that delay the final act of supplying discharge medication. Purpose: To determine whether accredited pharmacists improve timing and accuracy of discharge by reconciling TTA medication. 100% of TTAs reconciled by pharmacists will contain no discrepancies. 70% of discharge prescriptions written at least a day in advance of a patient's discharge. 70% of discharge prescriptions not changed after dispensing completed. Material and methods: Baseline data were collected prospectively for 2 weeks in July 2015 on one cardiothoracic ward prior to implementation of the MROD policy. The audit was repeated over a 2 week period in September 2015 whereby an accredited pharmacist reconciled discharge medication for medics to determine safety and efficacy. Ethics approval was not required. Results: Results of TTA discrepancies and relevant timings have been collated and displayed in table 1 . Conclusion: MROD by pharmacists led to a significant reduction in discrepancies compared with baseline. The majority of TTAs (72%) were unaltered after completion and most (72%) written at least 24 h prior to discharge, suggesting pharmacy led MROD is both safer and more effective than conventional discharge process. References and/or Acknowledgements: Gross, Z. How pharmacists help speed up the discharge process to release beds. Pharm J, 2001. Available at http://www.pharmaceutical-journal.com/news-and-analysis/feature/how-pharmacists-help-speed-up-the-discharge-process-to-release-beds/20005441.article (accessed 06/09/15) No conflict of interest.